Fenomena “thrifting” menjelang hari raya dan return saham industri tekstil - Hutagalung, Deswita Natalia Br; Agatha , Glorya (Riset Akuntansi dan Portofolio Investasi, 2023)
The thrifting phenomenon is an issue that spread in the textile and garment industry. The objective of this study is to examine the effect of religious holidays in the thrifting phenomenon on stock returns, especially for firms engaged in the textile and garment business. The observation period of this study is November 21, 2022, to April 18, 2023, which is divided into three sub-periods, which are period leading up to Christmas and New Year 2022-2023, the non-holiday period, and the period leading up to Lebaran. This study finds that the returns of the firms in the textile and garment business are less than optimal in the three sub-periods. The findings of this study imply that religious holidays in the thrifting phenomenon contribute enough to the performance of returns even though it has an insignificant impact.